The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/ja806781u
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Employing Unstabilized Nucleophiles in Palladium-Catalyzed Asymmetric Allylic Alkylations

Abstract: We report a strategy for the employment of highly unstabilized anions in palladium-catalyzed asymmetric allylic alkylations (AAA). The "hard" 2-methylpyridyl nucleophiles studied are first reacted in situ with BF3.OEt2; subsequent deprotonation of the resulting complexes with LiHMDS affords "soft" anions that are competent nucleophiles in AAA reactions. The reaction is selective for the 2-position of methylpyridines and tolerates bulky aryl and alkyl substitution at the 3-, 4-, and 5-positions. Investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(73 citation statements)
references
References 14 publications
0
73
0
Order By: Relevance
“…of 21-25, respectively, with no further optimization of the reaction conditions. We found that vinylboronic acids can also be used as nucleophiles under the same reaction conditions (entries [25][26][27] to give 26-28, respectively. Here, good yields and high levels of enantioselectivity were observed when the reaction time was extended from one to four hours.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…of 21-25, respectively, with no further optimization of the reaction conditions. We found that vinylboronic acids can also be used as nucleophiles under the same reaction conditions (entries [25][26][27] to give 26-28, respectively. Here, good yields and high levels of enantioselectivity were observed when the reaction time was extended from one to four hours.…”
mentioning
confidence: 91%
“…Pd-catalysed processes that convert a racemic mixture of starting materials into a new single-enantiomer product are commonly referred to as dynamic kinetic asymmetric transformations (DYKATs), as originally developed by Trost and co-workers 24 . DYKATs can now be used with a wide variety of stabilized nucleophiles and an array of metal catalysts 24 and several non-stabilized sp 3 -hybridized nucleophiles can now be used in certain related procedures [25][26][27][28] .…”
mentioning
confidence: 99%
“…Ligand L5 has also shown very good results in the reaction of unstabilized nucleophiles [34]. As an example, a hard nucleophile was obtained from The Trost ligand analog L6 is another good ligand for decarboxylative allylic substitution.…”
Section: Trost's Ligandsmentioning
confidence: 99%
“…2 This narrow substrate scope reflects the inherent challenge of simultaneously forming vicinal stereocenters selectively. After reporting a method for employing 2-methylpyridines in palladium-catalyzed AAAs, 3 we wondered whether an analogous reaction with higher-order 2-substituted pyridines could be effected in a diastereo- and enantioselective fashion (Scheme 1, A ). We hypothesized that, upon coordination of the pyridyl nitrogen atom with BF 3 , benzylic deprotonation would provide a nucleophile that would exist as a single geometric isomer because of the steric demands imposed by the Lewis acid.…”
mentioning
confidence: 99%
“…Unfortunately, when 2-ethylpyridine ( 1 ) was reacted with allylic carbonate 2 under the previously optimized conditions, 3 1 H NMR revealed no desired product and partial decomposition of 2 (Scheme 1, B ). Replacing the tert -butyl carbonate ester with the more robust pivalate ester provided an electrophile that was completely stable to the reaction conditions, and with this substrate the desired alkylation product ( 3a ) could be obtained in 15% yield, >19:1 dr, and 95% ee.…”
mentioning
confidence: 99%